PoliFi: Airtime Policy Enforcement for WiFi - Toke Høiland-Jørgensen; Per Hurtig; Anna Brunstrom (Karlstad University, 2019)
This is the companion website to the paper "PoliFi: Airtime Policy Enforcement
for WiFi" by Toke Høiland-Jørgensen, Per Hurtig and Anna Brunstrom, which will
be presented at the 2019 IEEE Wireless Communications and Networking
Conference

Also published at https://www.cs.kau.se/tohojo/polifi/
Keywords: Computer Sciences; Datavetenskap (datalogi)